“Great writing always sings”: Dorothy Allison Speaks - Grué, Mélanie; Allison, Dorothy (The Southern Quarterly, 2016)
Brought up in a Southern poor white family and the victim of her stepfather's abuse from a very early age, Allison turned to writing to address difficult issues which few writers dare to deal with: child abuse, class-based discrimination, transgressive lesbianism, and overall violence. [...]I started burning them, or destroying them. Because they were just too dangerous to be in the world. Some of it is not so bad: bluegrass and rhythm 'n' blues, some of the gospel music I love, it stays with me.
Keywords: amériques; approches et analyses; patriarcat; personnes lesbiennes; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; écriture des femmes*; états-unis